Host country executives' assessments of international joint ventures and divestitures: An experimental approach - Tong, Tony W.; Reuer, Jeffrey J.; Tyler, Beverly B.; Zhang, Shujun (Strategic Management Journal, 2015)
A large body of research examines the modes by which multinational firms enter foreign markets, yet little work has considered how host country executives evaluate alternative modes of accepting inward foreign direct investment ( FDI ). This study adopts the host country firm's perspective to investigate the factors that affect C hinese executives' assessments of international joint ventures ( IJV s) and divestitures as different modes for engaging inward FDI opportunities. We use an experimental approach to test our argument that executives' preferences for IJV s versus divestitures are driven by multinational firms' resources as well as potential transaction hazards and available remedial mechanisms. This study complements extant research on firms' entry mode choice by offering a direct test of comparative economic organization by explicitly comparing the attractiveness of alternative modes . Copyright © 2013 John Wiley & Sons, Ltd.